2012
DOI: 10.3389/fgene.2012.00052
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of Metal Responsive Genes in Caenorhabditis elegans

Abstract: Metals are major contaminants that influence human health. Many metals have physiologic roles, but excessive levels can be harmful. Advances in technology have made toxicogenomic analyses possible to characterize the effects of metal exposure on the entire genome. Much of what is known about cellular responses to metals has come from mammalian systems; however the use of non-mammalian species is gaining wider attention. Caenorhabditis elegans is a small round worm whose genome has been fully sequenced and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…Comparison of the transcriptomics changes during Ag and SiO 2 exposures with the findings in previous studies on metal toxicities indicated that metallothionein-2 (mtl-2), a commonly observed responsive gene to the metal toxicities (conserved in C. elegans and mammals) (Caito et al, 2012;Cui et al, 2007;Roh, Lee & Choi, 2006;Kumar et al, 2015;Anbalagan et al, 2012), was up-regulated in these groups (FDR =0.002 for Ag, FDR = 0.043 for SiO2), which further confirmed the effectiveness of the model. Ag and SiO 2 nanoparticles have been shown to affect locomotion velocity in C. elegans N2, as previously described (Jung et al, 2015).…”
Section: Sio2supporting
confidence: 74%
See 1 more Smart Citation
“…Comparison of the transcriptomics changes during Ag and SiO 2 exposures with the findings in previous studies on metal toxicities indicated that metallothionein-2 (mtl-2), a commonly observed responsive gene to the metal toxicities (conserved in C. elegans and mammals) (Caito et al, 2012;Cui et al, 2007;Roh, Lee & Choi, 2006;Kumar et al, 2015;Anbalagan et al, 2012), was up-regulated in these groups (FDR =0.002 for Ag, FDR = 0.043 for SiO2), which further confirmed the effectiveness of the model. Ag and SiO 2 nanoparticles have been shown to affect locomotion velocity in C. elegans N2, as previously described (Jung et al, 2015).…”
Section: Sio2supporting
confidence: 74%
“…Furthermore, gene enrichment in GO and newly determined terms were carried out using GOATOOLS (Klopfenstein et al, 2018) and WormExp (Yang, Dierking & Schulenburg, 2016), respectively. Differentially expressed genes in the toxicity groups (compared to control) were further searched to ascertain whether they were reported in metal toxicity based on previous studies (Caito et al, 2012;Cui et al, 2007;Roh, Lee & Choi, 2006;Kumar et al, 2015;Anbalagan et al, 2012).…”
Section: Data Analysis For Rnaseqmentioning
confidence: 99%
“…The precise changes depended on coexposure to other secondary toxins (UVC and hydrogen peroxide), and whether the mercury was presented in organic or inorganic form. Caito and Aschner also showed that organic mercury (MeHg) caused mitochondrial dysfunction, decreased mitochondrial mass and mtDNA copy number (Caito et al 2012(Caito et al , 2013. Interestingly, they also showed that the effects were NAD + dependent and could be alleviated by pretreatment of the nematodes with exogenous NAD + .…”
Section: Toxicologymentioning
confidence: 99%
“…It is well known that metals can cause neurotoxicity, alter neuronal excitability, and impair chemosensation, and that they are involved in neurodegenerative diseases . Furthermore, free radicals and reactive oxygen species generated by metals can induce protein and deoxyribonuclease (DNA) oxidation and lipid peroxidation . They also disrupt cellular homeostasis by impairing DNA repair, inhibiting enzyme activity, and affecting protein binding .…”
Section: Introductionmentioning
confidence: 99%